Growth, longevity and mortality of pink shrimps Farfantepenaeus brasiliensis and F. paulensis in southeastern Brazil - Fernandes Perroca, Júlia [UNESP]; Miazaki, Lizandra Fernandes [UNESP]; Fransozo, Adilson [UNESP]; DE MORAES FREIRE, Fúlvio A.; Costa, Rogerio C. [UNESP] (Instituto Nacional de Investigacion y Desarrollo Pesquero (INIDEP), 2022)
The study estimated the parameters of growth, longevity, fishing mortality (F), natural mortality (M) and total mortality (Z) and the exploitation rates (E) of the shrimps Farfantepenaeus brasiliensis and F. paulensis sampled in Ubatuba Bay from January to December 2000. Shrimps were identified by species, sexed and measured (carapace length –CL in mm). Overall, 1,231 individuals of F. brasiliensis and 687 of F. paulensis were analyzed. The mean size between sexes did not differ for both species. The estimated parameters of F. brasiliensis were: CL∞ = 41.08 mm, k = 2.41 year-1 for males and CL∞ = 47.32 mm, k = 2.23 year-1 for females; longevity of 1.91 years (males) and 2.05 years (females); M of 2.47 (males) and 2.28 (females); F of 7.97 (males) and 8.42 (females). For F. paulensis, the following values were observed: CL∞ = 36.55 mm, k = 2.41 year-1 for males and CL∞ = 49.24 mm, k = 2.51 year-1 for females; longevity of 1.91 years (males) and 1.81 years (females); M of 2.52 (males) and 2.52 (females); F of 7.64 (males) and 10.25 (females). The high values of k and F found for both species compared to those from the literature reflected the high E values, indicating that at the time, the closed season was still not responsible for stock recovery. We highlight the need for studies to assess the current status of stocks so they can be compared to the results found herein.
Crecimiento, longevidad y mortalidad de camarones rosados Farfantepenaeus brasiliensis y F. paulensis en el sureste de Brasil
Keywords: Artisanal fishery; Bertalanffy; closed season; exploitation rate; Penaeidae